CHEMICAL EVOLUTION OF METAL IN REFRACTORY INCLUSIONS IN CV3 CHONDRITES - Campbell A.J.; Simon S.B.; Humayun M.; Grossman L. (My University, 2003)
Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) was used to measure distributions of the siderophile elements V, Fe, Co, Ni, Mo, Ru, Rh, Pd, W, Re, Os, Ir, Pt, and Au in Fremdlinge with a spatial resolution of 15 to 25 μm. A sulfide vein in a refractory inclusion in Allende (CV3-oxidized) is enriched in Rh, Ru, and Os with no detectable Pd, Re, Ir, or Pt, indicating that Rh, Ru, and Os were redistributed by sulfidation of the inclusion, causing fractionation of Re/Os and other siderophile element ratios in Allende CAIs. Fremdlinge in compact Type-A inclusions from Efremovka (CV3-reduced) exhibit subsolidus exsolution into kamacite and taenite and minimal secondary formation of V-magnetite and schreibersite. Siderophile element partitioning between taenite and kamacite is similar to that observed previously in iron meteorites, while preferential incorporation of the light PGEs (Ru, Rh, Pd) relative to Re, Os, Ir, and Pt by schreibersite was observed. Fremdling EM2 (CAI Ef2) has an outer rim of P-free metal that preserves the PGE signature of schreibersite, indicating that EM2 originally had a phosphide rim and lost P to the surrounding inclusion during secondary processing. Most Fremdlinge have chondrite-normalized refractory PGE patterns that are unfractionated, with PGE abundances derived from a small range of condensation temperatures, ∼1480 to 1468 K at Ptot = 10−3 bar. Some Fremdlinge from the same CAI exhibit sloping PGE abundance patterns and Re/Os ratios up to 2 × CI that likely represent mixing of grains that condensed at various temperatures.
Keywords: Chondrites